Phase change dynamics in a triangular elastic walled vented cavity having phase change material packed bed during nanofluid forced convection - Selimefendigil, Fatih; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Journal of Central South Univ, 2023)
In this study, phase change process dynamics in a triangular shaped elastic walled vented cavity is explored during nanofluid forced convection in the laminar flow regime. Impacts of Reynolds number (Re), Cauchy number (Ca) and port size of the cavity on the flow field and phase change dynamics are explored by finite element method. It is observed that the flow recirculation below the inlet port and phase change dynamics are affected by the variation of Re, Ca and port size. The phase transition time (TF) is reduced first when increasing Re from 100 to 200 and then increases. Hybrid nanofluid results in fast phase change while TF is reduced by about 26% at Re=100. Up to 12.5% reduction of TF is achieved at the highest value of Ca. The port size has a negative impact on the phase transition while TF is increased up to 19% with varying the port size.
Keywords: phase change process; elastic wall; nanofluid; finite element method